Platelet‐rich plasma counteracts detrimental effect of high‐glucose concentrations on mesenchymal stem cells from Bichat fat pad. (8th April 2020) - D'Esposito, Vittoria; Lecce, Manuela; Marenzi, Gaetano; Cabaro, Serena; Ambrosio, Maria Rosaria; Sammartino, Gilberto; Misso, Saverio; Migliaccio, Teresa; Liguoro, Pasquale; Oriente, Francesco; Fortunato, Leonzio; Beguinot, Francesco; et al.
Abstract: Diabetic patients display increased risk of periodontitis and failure in bone augmentation procedures. Mesenchymal stem cells (MSCs) and platelet‐rich plasma (PRP) represent a relevant advantage in tissue repair process and regenerative medicine. We isolated MSCs from Bichat's buccal fat pad (BFP) and measured the effects of glucose and PRP on cell number and osteogenic differentiation potential. Cells were cultured in the presence of 5.5‐mM glucose (low glucose [LG]) or 25‐mM glucose (high glucose [HG]). BFP–MSC number was significantly lower when cells were cultured in HG compared with those in LG. Following osteogenic differentiation procedures, calcium accumulation, alkaline phosphatase activity, and expression of osteogenic markers were significantly lower in HG compared with LG. Exposure of BFP–MSC to PRP significantly increased cell number and osteogenic differentiation potential, reaching comparable levels in LG and in HG. Thus, high‐glucose concentrations impair BFP–MSC growth and osteogenic differentiation. However, these detrimental effects are largely counteracted by PRP.